SiCl4-Modified H-ZSM-5 As Support In Bimetallic Chromium-Copper Catalyst For The Combustion Of VOCs In Air Stream. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2005)
The performance of silicon tetrachloride (SiCl4) modified H-ZSM-5 (Si/Al=240) as support to bimetallic chromium-copper catalyst for the combustion of non-chlorinated and chlorinated volatile organic compounds (VOCs) is reported.